2015
DOI: 10.5513/jcea01/16.3.1627
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative growth and fruit set of olive (Olea europaea L. cv. �Zard�) in response to some soil and plant factors

Abstract: This experiment was conducted to explore the reasons of difference between 'Zard' olive orchard with the poor vegetative growth rate and fruit set and orchard with suitable vegetative growth rate and fruit set in relation to some soil and plant factors during two seasons. Note that assumptions were based on the overall canopy greenness of the olive trees, so experimental orchards in which the planted trees showed optimum leaf greenness were considered good situations for optimum vegetative growth and productiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…The use of remote sensing has contributed significantly to this area. Remote sensing technologies based on Normalized Difference Vegetation Index (NDVI) combining soil and plant factors were employed on two olive orchards in order to investigate the fruit set [20]. Masilli et al [21] developed a methodology incorporating meteorological data and remote sensing data for the assessment of Tuscany olive groves' production.…”
Section: Introductionmentioning
confidence: 99%
“…The use of remote sensing has contributed significantly to this area. Remote sensing technologies based on Normalized Difference Vegetation Index (NDVI) combining soil and plant factors were employed on two olive orchards in order to investigate the fruit set [20]. Masilli et al [21] developed a methodology incorporating meteorological data and remote sensing data for the assessment of Tuscany olive groves' production.…”
Section: Introductionmentioning
confidence: 99%
“…The level of photosynthesis in olive trees was possibly limited by low water absorption in medium salinity. Munns (1993) mentioned that the toxic effect of salt accumulation would be visible at higher Na + or Clconcentrations. Kchaou et al (2010) identified that the 'Chemlali', which tolerated salinity (100 mM NaCl), along with the 'Chetoui' cultivar, are good choices for cultivation in saline conditions.…”
Section: Discussionmentioning
confidence: 99%